The Terebelliformia-Recent Developments and Future Directions - Pat Hutchings; Orlemir Carrerette; João M. M. Nogueira; Stephane Hourdez; Nicolas Lavesque (Diversity, 2021)
Terebelliformia comprises a large group of sedentary polychaetes which live from the intertidal to the deep sea. The majority live in tubes and are selective deposit feeders. This study synthesises the current knowledge of this group, including their distribution, in the different biogeographic regions. We highlight the new methodologies being used to describe them and the resolution of species complexes occurring in the group. The main aim of this review is to highlight the knowledge gaps and to stimulate research in those directions, which will allow for knowledge of their distribution and abundances to be used by ecologists and managers.